Bentuk Teologi Mengenai Doktrin Allah dalam Konsep Kekristenan - Rossan Kurnia; Mirna Widianti; Prita Aura Eklesia; Sarmauli Sarmauli (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
The doctrine of God consists of five main topics, namely theological guidance, the existence of Allah, the attributes of God, the names of God and the works of God. The aim of understanding the doctrine of God is to recognize God from a Christian perspective, as well as the nature and identity of God, understanding the Triune God, and also the attributes of God. The method used is a qualitative method using a literature review containing books containing the doctrine of God, as well as several supporting journals in discussing this doctrine. From this research, there were findings regarding the view of God in Christianity in the form of a different understanding of how God manifests Himself as well as the qualities or things found in God based on the contents of the Bible. Even though God cannot truly be understood in its entirety through understanding the human mind, we can understand God's existence through the truth contained in the Bible.